Kreativitas Guru dan Media Berbasis Proyek untuk Atasi Keterbatasan Alat Peraga - Putri Nazarina; Yuli Rahmawati; Nurul Arifah; Tasya Langgari; Nur Annisa (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
This study aims to examine the role of teacher creativity and project-based media in addressing the limitations of teaching aids in primary schools, particularly within the context of the Merdeka Curriculum. The method employed is a Systematic Literature Review (SLR) with a qualitative approach, involving the analysis of 21 relevant empirical studies on this topic. The findings indicate that teacher creativity plays a key role in creating innovative learning media, especially by utilizing local resources to overcome the limitations of teaching aids. Project-based learning media have proven effective in enhancing student engagement, promoting the development of 21st-century skills such as creativity, collaboration, and critical thinking, and creating more contextual and meaningful learning experiences. However, teachers still face several challenges, such as limited resources, lack of training, and low student motivation. This study recommends solutions such as intensive teacher training, the development of a flexible curriculum, cross-sector collaboration, and the provision of adequate resources to support the implementation of project-based learning media. In conclusion, with the right strategies, project-based learning media can serve as an effective approach to improve the quality of education in primary schools, despite the limitations of teaching aids.